Depletion of Iron Stores and Main Associated Parameters in Adolescents of Côte d’Ivoire - Atto, Virginie; Bleyere, Mathieu N.; Konan, Andre B.; Datte, Jacques Y.; Yapo, Paul A. (Pakistan Journal of Nutrition, 2013)
In Côte d’Ivoire, very few studies are devoted to the exploration of iron status in adolescents for early screening of iron deficiency and anaemia. This study aims to assess the iron status in adolescents aged 12 to 18 years apparently healthy living in Abidjan (Côte d’Ivoire). It also intended to identify the influence of infectious and inflammatory syndromes on indicators of iron status. Eight hundred and forty seven (847) adolescents enrolled in three municipalities of Abidjan, blood samples were carried out for the determination of biological parameters of iron status. Our study indicated that about three on four adolescents have abnormal iron status. This abnormal iron status is composed of 33.9 of iron deficiency, 30% iron deficiency anaemia, 6% of inflammatory anaemia and 4.7% of inflammatory anaemia associated with iron deficiency. The prevalence of infections and inflammatory disorders is also observed in adolescents. In addition, Pearson coefficients correlation indicated a significantly positive correlation of C Reactive Protein (CRP) with serum ferritin. The main cause of pronounced degradation in iron status is insufficient in the size of iron stores. The problem of the iron metabolism alteration is important in the Côte d’Ivoire in adolescents.